6. Variables and Constants in the Curriculum for the Music Specialisations of the Romanian University Education - Paşca Eugenia Maria (Sciendo, 2016)
The Romanian academic system must adapt to the changing demands imposed by the European educational standards, according to the conventions of Bologna and Lisbon. The compatibilisation of university paths in creating the curricula must consider the competences which are to be acquired. The responsibility belongs equally to the institutions providing academic programs, but also to the Romanian Agency for Quality Assurance in Higher Education. We intend to analyse comparatively both the constant and variable elements of the academic programs for the Music field. The efficiency of these programs is particularly reflected from the point of view of insertion in the labour market, so the direct beneficiaries are the graduate students.